The reality of applying the principles of university governance at the University of Idlib from the Perspective of Faculty Members - Staif, Ahmad Mohamad; Abdulaziz, Siham Mustafa; Abd Alsid, Hisham Farag (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of application of governance principles (participation, transparency, accountability) from the point of view of faculty members at the University of Idlib. To achieve the goal of the study, the researcher used the descriptive analytical method, and the study tool was a questionnaire consisting of (28) items distributed over 3 axes: Participation (8) items, transparency (10) items, accountability (10) items. The questionnaire was sent to the entire study community, which numbered (162) members, of whom (43) faculty members at the University of Idlib responded. The study concluded that the degree of application of the principles of governance (participation, transparency, and accountability) at the University of Idlib from the point of view of faculty members was average on the three principles, with an arithmetic mean that ranged between (3.25-2.67), and a medium degree of application. Where the principle of transparency came in the first place with an arithmetic average of (3.25), in the second place the principle of accountability with an arithmetic mean of (3.19), and in the third place the principle of participation with an arithmetic mean of (2.67). This result indicates that the University of Idlib applies the three principles of governance, but not at the required level. The study also found that there are no statistically significant differences in the degree of application of the principles of governance (participation, transparency, accountability) from the point of view of faculty members at Idlib University due to the variables of academic qualification. (Masters, Ph.D.), and also that there were no statistically significant differences due to the college variable (human, scientific).
Keywords: principles of governance; participation; transparency; accountability; University of Idlib